Study on the properties of soil mixture between shredded tire and cohesive frictional soil/Mohammad Shafawi Abdullah - Abdullah, Mohammad Shafawi (Faculty Of Civil Engineering, 2005)
The trend in the used of waste materials such as Fly Ash, Fluorogypsum, and Shredded Tire as mixers with the soil in the modern engineering construction shows the awareness and responsibility among researchers and engineers in protecting and improving the quality of environment. Thus, its behavior in stabilizing the soil needs to be understood clearly. In this project, the characteristic of the soil mixture shredded tire mixes with cohesive frictional soil were studied. Standard testing according to the British Standard for soil properties were carried out on the mixtures of cohesive frictional soil on the mixtures of cohesive frictional soil and shredded tires which are 10%, 30%, 50% and 70% of dry weight of cohesive soil. Tests also conducted on 100% of shredded tires and 100% of cohesive frictional soil for control purpose. Based on the result obtained, it was found that for 10% mixture of shredded tires, shear strength of materials increased around 3.2% and the density reduced around 11.25% from 100% of cohesive frictional soil. For other mixtures, it shown that both of shear strength and density reduced from 100% of cohesive frictional soil.